The era of sharing economy: factors that influence the behavioral intentions of user and provider to participate in peer-to-peer sharing economy - Raza, Aleem; Asif, Muhammad; Ayyub, Samia (Serbian Journal of Management, 2021)
The Sharing Economy is a fastest growing and heavily debated Socio economic model. In the platform-based sharing economy, the provider provides the service and the consumer using the service from a two-sided market. However, there is a lack of studies that cover the both sides of platform based sharing market. This study aims to examine the effect of Indulgence, trust, economic benefit, social interaction, enjoyment and sustainability on user and provider intention to engage in peer-to-peer sharing. This explanatory study uses a quantitative methodology involving data collection through structured questionnaire from service users (n=220) and service providers (n=170) of Uber and Careem by adopting snowball sampling technique. Structured Equation Modeling (SEM) was applied to analyze data by using AMOS 24. The empirical results of this study indicate that indulgence, social interaction, economic benefit and enjoyment have significant positive association with user and provider intention. Further, a positive relationship was found between provider trust in user and provider intention to engage in peer-to-peer sharing. This study makes its significant contribution by providing new insights to literature and practice by studying two sided market. In addition the study explored the effect of indulgence on peer-to-peer sharing intention which is found yet to be explored in the literature. This study suggests practical implications for the Marketing managers to develop effective platform business strategies and marketing campaigns in accordance with the individuals’ intention to engage in sharing.